Analytical expressions for estimating endurance time and glove thermal resistance related to human finger in cold conditions. (October 2017) - Fallahi, Amir; Salimpour, Mohammad Reza; Shirani, Ebrahim
Abstract: Frostbite is considered the severest form of cold injury and can lead to necrosis and loss of peripheral appendages. Therefore, prediction of endurance time of limb's tissue in cold condition is not only necessary but also crucial to estimate cold injury intensity and to choose appropriate clothing. According to the previous work which applied a 3-D thermal model for human finger to analyze cold stress, in this study, an expression is presented for endurance time in cold conditions to prevent cold injury. A formula is also recommended to select a proper glove with specific thermal resistance based on the ambient situation and cold exposure time. By employing linear extrapolation and real physical conditions, the proposed formulas were drawn out from numerical simulation. Analytical results show good agreement with numerical data. The used numerical data had been also validated with experimental data existed in the literature. Furthermore, the effect of different parameters such as glove thermal resistance and ambient temperature is investigated analytically. Highlights: A novel approach is engaged to extract analytical correlations from numerical data. Expressions are suggested for prediction of endurance time and glove resistance. The expressions provide vital information for studying the frostbite phenomenon.